ASSESSMENT OF THE SOCIO-ECONOMIC SITUATION OF REGIONS USING THE ZIPF LAW - Kabanov, Vadim; Larionov, Dr. Arkady (Revista Inclusiones, 2021)
The approval of the spatial development strategy of Russia encourages the activities of regional public authorities to develop strategic development documents. The regulations adopted by the Federal center do not define the tools necessary for scientific justification of long-term development goals of the Rus-sian Federation’s subjects. This paper offers a simple tool for assessing the socioeconomic develop-ment of Russian regions that can be used to determine the potential of the regional economy. Objective: to determine the dynamics of changes in the socio-economic position of regional leaders in the Russian Federation by comparing the quantitative values of 3 indicators with an inversely proportional function (Zipf’s law). The paper presents a solution to the problem of forming quantitative initial values. Statis-tical observations of Rosstat are the only source of information that has the highest level of reliability. The quantitative values of the considered indicators are published annually by the state statistics bod-ies. Standard methods of mathematical statistics were used in this work. By changing the value of the coefficient of determination for each array of quantitative values, the speed of approximation of the dis-tribution to Zipf’s law is determined. Convincing evidence is given for approximating distributions of quantitative indicators to an inversely proportional function (Zipf’s law). This conclusion can be used in the formation of long-term goals of socio-economic development in systems that are a set of territori-al entities. The results obtained coincide with the published conclusions on the feasibility of applying the Zipf’s law in the study of socio - economic situation in systems that are a set of territorial entities.